?Effect of additive level on potato sprout suppression at high temperature by dust formulations of tecnazene (Biological Sciences - PJSIR, 1995)
Currently used post-harvest applied commercial formulationsof potato sprout inhibitors show a degree of effectivenessat relatively low temperatures of 8 - lO°e. Attemptshave already been made to store potato tubers at around24°C with sprout suppressant [1].